2017
DOI: 10.1108/jima-08-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of Islamic banking services in Malaysia

Abstract: Purpose-The purpose of this paper is to examine the level of understanding of Islamic banking concepts and the factors that influence Islamic banking adoption in Malaysia, based on Rogers' (1983; 2003) Diffusion of Innovation. Specifically, the impact of perceived attributes and other variables (understanding, consumer innovativeness and bank personnel's professionalism) on Islamic banking adoption is examined. Design/methodology/approach-A quantitative approach using a sample of 200 working MBA students in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 40 publications
9
87
1
4
Order By: Relevance
“…The study found that KNW had significant positive effects on African Traditional (β= 0.50) followed by the Muslim (β= 0.25) and the least Christians (β= 0.19) sub-groups attitude towards IB. these results corroborate prior studies that Knowledge has influence on attitude towards IB (Mariadas et al, 2017;Mbawuni & Nimako, 2017;Nurdin, 2017;Mahdzan et al (2015;Abuazom et al, 2013;Abuazom et al, 2013) revealed in their study that the Islamic Bank embarks on knowledge sharing among employees and other motivations like promotion and reward system. Islamic Banks encourage their employees to share knowledge and information in order to reduce risk (risk-weighted assets) of the capital adequacy ratio (CAR).…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study found that KNW had significant positive effects on African Traditional (β= 0.50) followed by the Muslim (β= 0.25) and the least Christians (β= 0.19) sub-groups attitude towards IB. these results corroborate prior studies that Knowledge has influence on attitude towards IB (Mariadas et al, 2017;Mbawuni & Nimako, 2017;Nurdin, 2017;Mahdzan et al (2015;Abuazom et al, 2013;Abuazom et al, 2013) revealed in their study that the Islamic Bank embarks on knowledge sharing among employees and other motivations like promotion and reward system. Islamic Banks encourage their employees to share knowledge and information in order to reduce risk (risk-weighted assets) of the capital adequacy ratio (CAR).…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…Knowledge on IB is regarded as one of the key determinants of IB adoption (Mariadas et al, 2017;Nurdin, 2017;Mahdzan et al (2015;Abuazom et al, 2013;Abuazom et al, 2013) revealed in their study that the Islamic Bank embarks on knowledge sharing among employees and other motivations like promotion and reward system. Islamic Banks encourage their employees to share knowledge and information in order to reduce risk (risk-weighted assets) of the capital adequacy ratio (CAR).…”
Section: Knowledge On Ibmentioning
confidence: 99%
See 1 more Smart Citation
“…The study further discovered the age ranges from 19 to 50 for most of the bank customers. It is also consistent with literature as studies have shown that the age of various bank customers range from 21 to 50 representing most of bank customers are Generation X (Mahdzan et al, 2017;Khattak & Rehman, 2010).…”
Section: Measurement Of Variablessupporting
confidence: 78%
“…The model was modified by introducing two unique dimensions of social responsibility and innovation each dimension contain one item. Social responsibility and innovation were included in the model due to significant role of these dimensions in the formation of exceptional service quality (Mahdzan, Zainudin, & Au, 2017). Each item was provided with five scale likert options ranging from 1 (strongly disagree), 2 (disagree), 3 (neutral), 4 (agree) to 5 (strongly agree).…”
Section: Measurement Of Variablesmentioning
confidence: 99%